Knowledge management in the twenty-first century - Bernuy-Alva, Augusto (2014)
In the world, there is a spectacular development in the knowledge management, for example the conferences IC3K; in addition, the prestigious Massachusetts Institute of Technology relies on the MIT Center for Collective Intelligence to conduct research on how ICTS are changing the way people work; among others; then, an adequate knowledge management leads to create the conditions for the organization to learn, with different approaches, from the provision of timely information to systems that allow to solve complex problems; it is for this reason that they seek to create new ways to use resources and to achieve the development of systems aligned to new processes that allow us to improve the productivity, efficiency and effectiveness of the organizations, gaining a sustainable competitive advantage. This article presents the models and strategies that allow you to use the technology trends to develop new systems that improve the productivity and organizational efficiency.